2020
DOI: 10.1016/j.medcle.2020.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Infection and thrombosis associated with COVID-19: Possible role of the ABO blood group

Abstract: Background SARS-CoV-2 infection is clinically very heterogeneous, varying from asymptomatic to severe clinical conditions with a fatal outcome. Some studies suggests that the ABO blood group could be a biological marker of susceptibility for the development of the disease. Material and methods We collected data from patients admitted with COVID-19 infection who had ABO blood group recorded, and analyzed the incidence by groups, compared with the global population in Nav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 11 publications
2
22
0
Order By: Relevance
“…( A ) Blood group O odd ratios (ORs) of COVID-19 relative to the other blood groups and blood group O frequencies at various geographical locations. Odd ratios were obtained from the works in [ 1 , 2 , 3 , 6 , 9 , 10 , 11 , 14 , 17 , 18 , 19 , 22 , 24 ], and the frequencies of blood group O were those reported in the groups of controls of the corresponding studies, representing frequencies in the local populations. OR values in populations where frequencies of blood group O are below and above 40% (O < 0.4 and O > 0.4, respectively) were compared by a two-tailed Mann–Whitney test.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…( A ) Blood group O odd ratios (ORs) of COVID-19 relative to the other blood groups and blood group O frequencies at various geographical locations. Odd ratios were obtained from the works in [ 1 , 2 , 3 , 6 , 9 , 10 , 11 , 14 , 17 , 18 , 19 , 22 , 24 ], and the frequencies of blood group O were those reported in the groups of controls of the corresponding studies, representing frequencies in the local populations. OR values in populations where frequencies of blood group O are below and above 40% (O < 0.4 and O > 0.4, respectively) were compared by a two-tailed Mann–Whitney test.…”
Section: Figurementioning
confidence: 99%
“…Thus, soon after the beginning of the pandemic a publication from Wuhan, China, reported a higher risk of infection for people of blood group A, and inversely a lower risk for people of blood group O [ 1 ]. Since then, associations with the ABO blood groups have been described in several additional publications from China as well as many other locations from Asia, the Middle East, Europe, and North America [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. Associations between ABO phenotypes were described with either the risk of infection or disease severity, although most studies did not explicitly separate these two aspects.…”
Section: Introductionmentioning
confidence: 99%
“…Countries with higher A phenotype and Rh negative blood group showed higher values of the prevalence and mortality rate [5]. However, studies on the association between COVID-19 and ABO phenotypes are at preliminary stage and the results are controversial [15][16][17][18][19][20][21][22][23][24][25][26][27][28].…”
mentioning
confidence: 99%
“…Marcos et al studied 226 patients and found lower incidence of COVID-19 and thrombosis in blood group O when compared to general population [ 29 ]. We did not observe lower rates of venous thrombosis or embolism in blood group O.…”
Section: Discussionmentioning
confidence: 99%